Extension and new area - Most General Case

Geometry Level 2

Given A B C \triangle ABC , a new triangle A B C \triangle A'B'C' is generated as follows:

  • Extend A B AB to B B' such that B B = b A B B B' =b \hspace{2pt} A B
  • Extend B C BC to C C' such that C C = c B C C C' =c \hspace{2pt} BC
  • Extend C A CA to A A' such that A A = a C A AA' =a \hspace{2pt} CA

where a , b , c a, b, c are positive scalars.

Find the ratio of the area of the new triangle to the original triangle, i.e. find [ A B C ] [ A B C ] \dfrac{[A'B'C']}{[ABC]}

1 + a 2 + b 2 + c 2 1 + a^2 + b^2 + c^2 ( 1 + a ) ( 1 + b ) ( 1 + c ) (1 + a)(1 + b)(1 + c) ( 1 + a + b + c ) 2 (1 + a + b + c)^2 1 + a + b + c + a b + a c + b c 1 + a + b + c + a b + a c + bc

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

X X
Jul 2, 2020

We can cut the triangle as in the previous problems, or we can use barycentric coordinates.

Let A = ( 1 , 0 , 0 ) , B = ( 0 , 1 , 0 ) , C = ( 0 , 0 , 1 ) A=(1,0,0),B=(0,1,0),C=(0,0,1) , then B = ( b , 1 + b , 0 ) , C = ( 0 , c , 1 + c ) , A = ( 1 + a , 0 , a ) B'=(-b,1+b,0), C'=(0,-c,1+c), A'=(1+a,0,-a) .

The ratio of the areas can be expressed as a determinant det ( 1 + a 0 a b 1 + b 0 0 c 1 + c ) \text{det} \left(\begin{array}{c}1+a & 0 & -a\\-b & 1+b & 0\\ 0&-c&1+c\end{array}\right)

This simplfies to ( a + 1 ) ( b + 1 ) ( c + 1 ) a b c = 1 + a + b + c + a b + b c + c a (a+1)(b+1)(c+1)-abc=1+a+b+c+ab+bc+ca

Let A B = x AB=x , B C = y BC=y , C A = z CA=z . Then, B B = b x BB'=bx , C C = c y CC'=cy , A A = a z AA'=az .

Moreover, let [ A B C ] = S \left[ {ABC} \right] = S , [ B B C ] = S 1 \left[ {BB'C'} \right] = {S_1} , [ C C A ] = S 2 \left[ {CC'A'} \right] = {S_2} , [ A A B ] = S 3 \left[ {AA'B'} \right] = {S_3} and [ A B C ] = S \left[ {A'B'C'}\right]=S' .

Then,
S 1 S = 1 2 B B B C sin ( 18 0 θ ) 1 2 B A B C sin θ = b x ( y + c y ) x y = b x y ( 1 + c ) x y = b + b c \frac{{{S_1}}}{S} = \frac{{\bcancel{{\frac{1}{2}}}BB' \cdot BC' \cdot \cancel{{\sin \left( {180^\circ - \theta } \right)}}}}{{\bcancel{{\frac{1}{2}}}BA \cdot BC \cdot \cancel{{\sin \theta }}}} = \frac{{bx \cdot \left( {y + cy} \right)}}{{x \cdot y}} = \frac{{bxy\left( {1 + c} \right)}}{{xy}} = b + bc Similarly, S 2 S = 1 2 C C C A sin ( 18 0 φ ) 1 2 C B C A sin φ = c y ( z + a z ) y z = c y z ( 1 + a ) y z = c + c a \frac{{{S_2}}}{S} = \frac{{\frac{1}{2}CC' \cdot CA' \cdot \sin \left( {180^\circ - \varphi } \right)}}{{\frac{1}{2}CB \cdot CA \cdot \sin \varphi }} = \frac{{cy \cdot \left( {z + az} \right)}}{{y \cdot z}} = \frac{{cyz\left( {1 + a} \right)}}{{yz}} = c + ca S 3 S = 1 2 A A A B sin ( 18 0 ω ) 1 2 A C A B sin ω = a z ( x + b x ) z x = a z x ( 1 + b ) z x = a + a b \frac{{{S_3}}}{S} = \frac{{\bcancel{{\frac{1}{2}}}AA' \cdot AB' \cdot \cancel{{\sin \left( {180^\circ - \omega } \right)}}}}{{\bcancel{{\frac{1}{2}}}AC \cdot AB \cdot \cancel{{\sin \omega }}}} = \frac{{az \cdot \left( {x + bx} \right)}}{{z \cdot x}} = \frac{{azx\left( {1 + b} \right)}}{{zx}} = a + ab

Adding,

S 1 + S 2 + S 3 S = a + b + c + a b + b c + c a \frac{{{S_1} + {S_2} + {S_3}}}{S} = a + b + c + ab + bc + ca

Hence,

S S = S S S + 1 = S 1 + S 2 + S 3 S + 1 = 1 + a + b + c + a b + b c + c a . \frac{{S'}}{S} = \frac{{S' - S}}{S} + 1 = \frac{{{S_1} + {S_2} + {S_3}}}{S} + 1 = \boxed{1 + a + b + c + ab + bc + ca}.

David Vreken
Jul 2, 2020

Let T T be the area of A B C \triangle ABC .

If A A = a C A AA' = aCA , then B A A \triangle BAA' has the same height as A B C \triangle ABC but a base of a C A aCA instead of C A CA , so B A A \triangle BAA' has an area of a T aT .

If B B = b A B BB' = bAB , then C B B \triangle CBB' has the same height as A B C \triangle ABC but a base of b A B bAB instead of A B AB , so C B B \triangle CBB' has an area of b T bT .

If C C = c B C CC' = cBC , then A C C \triangle ACC' has the same height as A B C \triangle ABC but a base of c B C cBC instead of A B AB , so A C C \triangle ACC' has an area of c T cT .

Also if A A = a C A AA' = aCA , then C A A \triangle C'AA' has the same height as A C C \triangle ACC' but a base of a C A aCA instead of C A CA , so C A A \triangle C'AA' has an area of a c T acT .

Also if B B = b A B BB' = bAB , then A B B \triangle A'BB' has the same height as B A A \triangle BAA' but a base of b A B bAB instead of A B AB , so A B B \triangle A'BB' has an area of a b T abT .

Also if C C = c B C CC' = cBC , then B C C \triangle B'CC' has the same height as C B B \triangle CBB' but a base of c B C cBC instead of B C BC , so B C C \triangle B'CC' has an area of b c T bcT .

Therefore, the ratio of areas of A B C \triangle A'B'C' to A B C \triangle ABC is T + a T + b T + c T + a b T + a c T + b c T T = 1 + a + b + c + a b + a c + b c \frac{T + aT + bT + cT + abT + acT + bcT}{T} = \boxed{1 + a + b + c + ab + ac + bc} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...